2022
DOI: 10.3390/brainsci12081057
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of NLRP Inflammasome in Neuropsychiatric Disorders

Abstract: The NLRP inflammasome is a multi-protein complex which mainly consists of the nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain. Its activation is linked to microglial-mediated neuroinflammation and partial neuronal degeneration. Many neuropsychiatric illnesses have increased inflammatory responses as both a primary cause and a defining feature. The NLRP inflammasome inhibition delays the progression and alleviates the deteriorating effects of neuroinflammation on several neurops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 136 publications
1
6
0
Order By: Relevance
“…The current study found evidence of significant associations between the prevalence of depressive disorders -major depressive disorder (MDD) and dysthymia -and the prevalence of both Alzheimer's disease and Parkinson's disease at a cross-national level. These results are consistent with existing research on the shared pathogenic mechanisms for these disorders [55][56][57][58], as well as with the results of longitudinal research in individual countries demonstrating a prospective link between depressive disorders and neuro-degenerative disorders [59][60][61][62]. Prior evidence suggests that the links between depression, Parkinson's disease and Alzheimer's disease are mediated by both genetic vulnerability [63][64][65] and exposure to environmental risk factors, such as stress and environmental toxins [66][67][68].…”
Section: Discussionsupporting
confidence: 89%
“…The current study found evidence of significant associations between the prevalence of depressive disorders -major depressive disorder (MDD) and dysthymia -and the prevalence of both Alzheimer's disease and Parkinson's disease at a cross-national level. These results are consistent with existing research on the shared pathogenic mechanisms for these disorders [55][56][57][58], as well as with the results of longitudinal research in individual countries demonstrating a prospective link between depressive disorders and neuro-degenerative disorders [59][60][61][62]. Prior evidence suggests that the links between depression, Parkinson's disease and Alzheimer's disease are mediated by both genetic vulnerability [63][64][65] and exposure to environmental risk factors, such as stress and environmental toxins [66][67][68].…”
Section: Discussionsupporting
confidence: 89%
“…In autoinflammatory diseases, the deregulated innate immune response to exogenous or endogenous danger signals triggers activation of the inflammasome, which typically determines the overactivation and release of IL-1 and IL-18 [105]. Autoinflammatory triggers include signals from damaged cells (danger associated molecular patterns-DAMPs), pathogen derived molecules, such as PAMPs, LPS and unmethylated CpG DNA, but also metabolites, such as glucose, free fatty acids, oxidized low-density lipoprotein (oxLDL), cholesterol crystals, uric acid crystals, ceramide, amyloid-β, α-synuclein and prion protein or superoxide dismutase [105,106]. PAMPs are recognized by the transmembrane and intracellular Pattern Recognition Receptors (PRRs), prototypes of the former and of the latter being the TLRs and the NOD-like receptor (NLR) family respectively [107].…”
Section: Danger Signals and Receptorsmentioning
confidence: 99%
“…Indeed, the inflammasome binds pathogenassociated and/or danger-associated molecular patterns, specific molecular motifs carried by gut microorganisms. Thus, a perturbation of the GM composition could overstimulate the inflammasome and compromise the GBA homeostasis, promoting neuroinflammation as seen in multiple sclerosis [36], Alzheimer's disease [37], Parkinson's disease [38], neuropsychiatric disorders [39], and sepsis [25,26]. While no human studies are available, a recent preclinical study has shown how the GM plays a part in sepsis-associated encephalopathy by improving neurological outcomes when indole-3-propionic acid, a microbial neuroprotective metabolite, is produced, leading to the inhibition of NLRP3 inflammasome activation and IL-1β secretion in the microglia [26].…”
Section: The Gut-brain Axismentioning
confidence: 99%